Environmental indicators in metal mining - Lottermoser, Bernd G., 1961- (Springer, 2017)
This book represents an important new contribution to the literature that presents practical and comprehensive solutions to mining activities. Its timely content has been prepared by several experts from around the world and its practical format addresses the major environmental predictive techniques required for the extraction and processing of metal resources. Packed with reviews and case studies, it covers current methods used to forecast environmental effects of metal mining.
Keywords: Mines and mineral resources -- Environmental aspects.; Mineral industries -- Environmental aspects.; Environmental indicators.; elektronické knihy; electronic books